(untitled) (مجلة ديالى للبحوث الانسانية, 2021)
Conflict is inevitable for humans. It is part of human nature. Especially, internal conflicts are an integral part of the daily life of a human being. The concept of internal conflict is considered the basis of all traditions of psychology, including the psychoanalytic theory of Sigmund Freud (1923/1942). The psychoanalytic applications upon literary works have been gaining importance nowadays. Therefore, psychoanalysis theory is a very effective method for analysing the “man vs. self” conflict in Fight Club (1996).